Preferencias de Scirtothrips dorsalis Hood 1919 (Thysanoptera: Thripidae) por diferentes estructuras de la planta del algodón (Gossypium hirsutum L.) en el valle cálido del Magdalena - Ebratt, Everth; Rodríguez, Andrés; Monje, Buenaventura; Varón, Edgar; Brochero, Helena; Goldarazena, Arturo (Universidad Nacional de Colombia, 2024)
Thrips samples were collected from cotton crops in the Andean region of the Magdalena warm valley, an area represented by the Colombian departments of Tolima, Huila and Cundinamarca. Ten cotton plants were randomly selected per hectare in each plot. Five young leaves, five floral buds, five opened flowers and five bolls or fruits were inspected. Immature stages were separated from the adults and a first classification was made according to the present thrips morphotypes, separating the adults of possible S. dorsalis specimens from the others. T-Student and Kruskal-Wallis tests were performed in order to find statistical differences between the different evaluated variables. The selectivity of S. dorsalis for each plant structure was determined by Z tests, Spearman correlation analysis and the Bray-Curtis similarity index. Scirtothrips dorsalis was found in 77% (n = 46) of the inspected sites. The species exhibited greater affinity to the boll, followed by young leaves and buds. Opened flowers constituted a resource not frequented by the pest with a similarity range of I = 0.8 (<1). It is suggested that cotton plants are hosts to the thrips species; it means that the pest life cycle is highly associated to the cotton production in the Andean region. The importance of the results related to the cotton production and other crops associated to the insect species in the region is discussed.